2015
DOI: 10.1016/j.procir.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-based Integrated Shop-floor Planning and Control of Manufacturing Operations for Mass Customisation

Abstract: The shift of traditional mass producing industries towards mass customisation practices is nowadays evident. However, if not implemented properly, mass customisation can lead to disturbances in material flow and severe reduction in productivity. This paper discusses the design and development of a Cloud-based production planning and control system for discrete manufacturing environments, referred to as i-MRP. The proposed approach takes into consideration capacity constraints, lot sizing and priority control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…The direct digital nature of AM combined with the use of cyber-physical systems will allow for cloud-based AM [186]. The benefits of cloud-based approaches have already been demonstrated in process optimization [320], adaptive process planning [235], shop-floor planning [234], scheduling [236], and maintenance [237]. The benefits of higher quality, hybrid, high DOF, cyber-physical, and cloud-based AM systems are expected to be emergent.…”
Section: New Manufacturing Paradigms and A Divergence Of Manufacturinmentioning
confidence: 99%
“…The direct digital nature of AM combined with the use of cyber-physical systems will allow for cloud-based AM [186]. The benefits of cloud-based approaches have already been demonstrated in process optimization [320], adaptive process planning [235], shop-floor planning [234], scheduling [236], and maintenance [237]. The benefits of higher quality, hybrid, high DOF, cyber-physical, and cloud-based AM systems are expected to be emergent.…”
Section: New Manufacturing Paradigms and A Divergence Of Manufacturinmentioning
confidence: 99%
“…SMEs in traditional industries exploit the cloud infrastructure by planning and controlling the production line, mass customization, shop scheduling, material planning, and improvement of production efficiency; see (J. Liu et al, 2019;Mourtzis et al, 2015;Shang et al, 2018;Udayangani et al, 2019) and references therein. Regarding the seventh research question, cloud infrastructure upgrades small/medium enterprise model to an extended business model that includes IT technologies and smart services without the expense of an in-house acquisition (Abdollahzadegan et al, 2013;Zheng et al, 2017).…”
Section: Collaborative Robots Complex Robotic Cells Interconnection and Safety Issuesmentioning
confidence: 99%
“…Liu et al (2011) reported an 'adaptive annealing GA' (AAGA) algorithm to deal with manufacturing planning problem of a job-shop. Mourtzis et al (2015) designed and developed i-MRP -a cloud-based manufacturing planning system for a discrete manufacturing environment. They considered capacity constraints, lot sizing and priority control in a continuous time environment.…”
Section: Mpc Approachesmentioning
confidence: 99%